Italian Political Cinema : Figures of the Long '68 - Resmini, Mauro, 1981- (Book collections on Project MUSE., 2022)
"Traditionally, the definition of political cinema assumes a relationship between cinema and politics, but Mauro Resmini sees this relationship as an impasse. He turns to Italian cinema to explore how films have reinvented the link between popular art and radical politics in Italy from 1968 to the early 1980s, a period of intense political and cultural struggles known as the long '68"--